EFEK MIRAS DALAM FOTOGRAFI EKSPRESI - Noviana Faizah; Surisman Marah; Arti Wulandari (Specta : Journal of Photography, Arts, and Media, 2022)
ABSTRACT Consumption of liquor has become a part of the socio-cultural of the people in Indonesia. There are many different types of local liquor. Groups of people who consume liquor generally have various reasons and backgrounds such as the need to warm the body, entertainment reasons and so on. The effect of liquor is an important aspect in the creation of the work, namely to capture the moment of expression of the drinking subject, as part of the photographer's medium of expression as well as the subject of photography. This creation is done by using the method of exploration and experimentation. Each stage that is carried out is based on a literature review, including expression photography, EDFAT and non-verbal semiotics. This is done as an effort to create art photos that are able to display the reality of expression as a potential in the aesthetic concept of photography. Keywords: Alcohol, Expression, Expression Photography